Pulp for health: Measuring consumer interest in avocado's nutritional properties - Daniela Spina; Manal Hamam; Raffaele Zanchini; Vincenzo Morreale; Raffaella Pergamo; Mario D'Amico; Giuseppe Di Vita (Journal of Agriculture and Food Research)
Avocado is one of the most traded, exported, and consumed tropical fruits worldwide. Its rich nutritional profile and associated health benefits have led to its classification as a superfood, enhancing its market appeal. This exploratory study empirically examines the elements that influence Italian consumers' interest in avocado's nutritional properties. Specifically, it considers the roles of objective and subjective knowledge, information exposure, nutritional components and extrinsic product characteristics, sensory properties, and socioeconomic factors. An online survey was conducted, resulting in a sample of 649 Italian consumers. The data were analyzed using an ordered logit model (OLM) and marginal effects estimation. The findings reveal that several factors including sensory attributes (taste, colour, and texture), nutritional components (fat, antioxidants, and minerals), and extrinsic characteristics (italian origin, certification, and price), influence consumers' interest in avocado's nutritional properties. Additionally, socioeconomic variables—particularly gender, education level, and sports participation—emerge as key determinants of perceived nutritional value. These insights have practical implications for market strategies and public health initiatives aimed at promoting avocado consumption.